Radiolabeled Peptides for SPECT and PET Imaging in the Detection of Breast Cancer: Preclinical and Clinical Perspectives - Fu, Hao; Du, Bulin; Chen, Zijun; Li, Yesen (Current Medicinal Chemistry, 2020)
Breast cancer is the most common cancer in women worldwide. Due to the heterogeneous nature of breast cancer, the optimal treatment and expected response for each patient may not necessarily be universal. Molecular imaging techniques could play an important role in the early detection and targeted therapy evaluation of breast cancer. This review focuses on the development of peptides labeled with SPECT and PET radionuclides for breast cancer imaging. We summarized the current status of radiolabeled peptides for different receptors in breast cancer. The characteristics of radionuclides and major techniques for peptide labeling are also briefly discussed.
Keywords: SPECT Imaging